2014
DOI: 10.1007/s13205-014-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic silver nanoparticles production and characterization from native stain of Corynebacterium species and its antimicrobial activity

Abstract: In the present study, synthesis, characterization, and the antibacterial activity of silver nanoparticles from native isolate of Corynebacterium glutamicum has been reported. Silver nanoparticles were synthesized by challenging the dried biomass of C. glutamicum with aqueous diamine silver ([Ag (NH3)2]+) containing 1 mM AgNO3. Synthesized silver nanoparticles (AgNPs) were characterized by ultraviolet–visible spectroscopy and energy-dispersive X-ray (EDX) spectroscopy analysis. Morphological study of silver nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…There are many sources of NP synthesis, but the green approaches are gaining popularity. Plant parts such as, the leaf, the bark, the flower, the peel, and the seed and microorganisms such as fungi, bacteria, algae, yeast, actinomycetes, and enzymes offer clean, eco-friendly, non-toxic machinery for their synthesis, which is compatible with pharmaceutical and cosmeceutical applications [9][10][11] . These NMs have long been documented to exhibit microbiocidal, microbiostatic actions and serve as potential antibacterial agents in medical and industrial applications [12] .…”
Section: Review Articlementioning
confidence: 99%
“…There are many sources of NP synthesis, but the green approaches are gaining popularity. Plant parts such as, the leaf, the bark, the flower, the peel, and the seed and microorganisms such as fungi, bacteria, algae, yeast, actinomycetes, and enzymes offer clean, eco-friendly, non-toxic machinery for their synthesis, which is compatible with pharmaceutical and cosmeceutical applications [9][10][11] . These NMs have long been documented to exhibit microbiocidal, microbiostatic actions and serve as potential antibacterial agents in medical and industrial applications [12] .…”
Section: Review Articlementioning
confidence: 99%
“…Green synthesis of NPs involving microorganisms and plants is noted to be safe, inexpensive, and environment-friendly as they absorb and accumulate inorganic metal ions from their surroundings leading to an unexplored field of useful research [186][187][188][189]. A number of biotechnological applications including bioremediation and bioleaching are possible to implement by exploiting the efficacy of the microorganisms to interact with the environment via their lipid-based amphipathic membranes enabling a variety of oxidation-reduction mechanisms occurring and promoting these biochemical conversions [190][191][192][193][194].…”
Section: Green Synthesismentioning
confidence: 99%
“…Generally, biological entities with a potential to accumulate heavy metals offer better chance of synthesizing metal NPs [200]. In case of microorganisms, optimization of parameters like nutrients, light, pH, temperature, mixing speed, and buffer strength used in their culture could significantly enhance the enzyme activity [188,201,202].…”
Section: Green Synthesismentioning
confidence: 99%
“…The findings reported that extracellular synthesis using plant extracts has been considered better as compared to intracellular (Makarov et al, 2014) because it abolish the extraction and purification methods. Green synthesis have been reported in Magnifera indica (Sandeep et al, 2017), Corynebacterium species (Gowramma et al, 2015).…”
Section: Introductionmentioning
confidence: 98%